PENINGKATAN KEMAMPUAN MENULIS PARAGRAF DESKRIPTIF SISWA KELAS X SMA NEGERI 02 BENGKULU TENGAH DENGAN MENGGUNAKAN METODE MENULIS BERANTAI (ESTAFET WRITING) - Puspita, Heni (Diksa : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2016)
The purpose of this study for improve the students class X1 skill of SMAN 2 Central Bengkulu Tengah in write descriptive paragraph with estafet writing method. This study design is the design of classroom action research conducted in two cycles, the first cycle and the second cycle. Collecting data on the first cycle and the second cycle using test technique and nontest. The test used is a test action in the form of assignment to write a description, whereas nontest techniques used in the form of guidelines for observation, the journal guidelines, interview guides, and photo documentation guidelines. Data analysis technique of this research is qualitative and quantitative. Quantitative techniques are used to analyze and compare test results pre-cycle, the first cycle, the second cycle, and qualitative techniques used to analyze and compare the results nontest in the first cycle and the second cycle. Based on the analysis of research data, in class X1 totaling 30 students can be concluded that by using the estafet writing method can increase the skill of writing a paragraph descriptive. In the first cycle, the value of an average of 71.65% in the second cycle, the average value of 88.73%, an increase of 17.08%. This means that there is an increase in the skill of writing a paragraph descriptive of the students with estafet writing method. This increase can be seen from the results of tests conducted students in class X SMAN 2 Central Bengkulu 2016/2017 school year that includes the end of the test cycle test cycle I and II.